Impact of energy crops on the quality of ecosystem services of Luvic Chernic Phaozem - Vodiak, Ya. N. (AgroChemistry and Soil Science, 2021)
The article presents the results of research on the impact of energy crops on the quality of such ecosystem services of Luvic Chernic Phaozem as providing, regulating and supporting. The observation was conducted during 2019-2020 in the SE "Experimental Farm "Grakivske", Novyi Korotych village in Kharkiv region of Ukraine. Energy perennial crops grown in the experiment: Miscanthus giganteus (plantings 2016 (I) and 2019 (II) years); Sida hermophrodita (2018); Silphium perfoliatum L. (2018). Control variables: determination of soil organic carbon content; pH level; number of microarthropods in the soil; plant stem length. An increase in organic carbon content was found in the upper soil layers beneath energy crop plants, especially in the root zone of Sylphium. Due to the root excretions of the crops a slight decrease in pH is also observed in all the variants compared to the control. A positive effect of the plants is also observed on the numbers of soil invertebrates – microarthropods, namely columbines and oribatids. The increase in their numbers indicates the formation of favorable conditions for these living creatures, in the root zone of all energy crops. For example, in May 2019 compared to the control (2706 ex. / m2) under four-year-old Miscanthus almost tripled (6126 ex. / m2), under annual Miscanthus – 4860 ex. / m2, under Sylphium – 5040 ex. / m2, and under Sida – 4320 ex. / m2. Positive changes in soil structure under the influence of Miscanthus giganteus cultivation, especially in the upper layer, were also noted. The coefficient of structure on the variants increased from 1.39 on the control, to 2.26 in layer 0-20 under Miscanthus. Measurements of stem height, showed that all of the selected crops were able to function normally despite reduced rainfall and increased temperatures in recent years. The plants are not depressed under drought conditions and only increase their biomass over time. Thus, the results indicate an overall improvement in the quality of soil ecosystem services in energy crop plantations. In particular, provisioning services – obtaining energy raw materials; regulating services – improving soil quality; and ecosystem services – depositing organic carbon, are improved.